A Suboptimal Discrete-Time Predictive Current Controller for a Voltage-Source Inverter - Kaynama, Shahab; Kukrer, Osman (IEEE, 2010)
This paper presents a discrete-time predictive control strategy for a voltage-source inverter based on computation of a deadbeat control law and its approximating suboptimal voltage vector at every sampling interval. The controller, in addition to compensating for the inherent delay in the system, employs a simple prediction filter to suppress the disturbance caused by the back-EMF voltages and improve robustness against parameter variations across the load. Discussions on the effect of the back-EMF prediction on the performance and robustness of the system is provided. It is shown that the proposed control strategy yields satisfactory transient and steady-state behavior and that the closed-loop system can tolerate a wide range of parameter variations and model uncertainty.
IEEE International Conference on Control Applications Part of 2010 IEEE Multi-Conference on Systems and Control -- SEP 08-10, 2010 -- Yokohama, JAPAN
Keywords: predictive control; current control; digital control; inverter